2008
DOI: 10.1590/s0047-20852008000300006
|View full text |Cite
|
Sign up to set email alerts
|

Uso de substâncias psicoativas entre universitários de medicina da Universidade Federal do Espírito Santo

Abstract: 2 . resultados: Ao todo, 54,8% dos universitários são do sexo feminino, 76,8% se encontram na faixa etária de 17 a 22 anos e 50% pertencem à classe social B. Quanto ao uso de substâncias psicoativas, 86,9% relataram uso na vida de álcool, seguido de tabaco (22,0%), solventes (15,5%), anfetaminas (10,1%), cannabis sativa (9,5%), alucinógenos com 1,8% e barbitúricos com 0,6%. conclusão: Faz-se necessária a prevenção do uso indevido de substâncias psicoativas entre universitários, por meio de disciplinas curricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
54

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 10 publications
1
8
0
54
Order By: Relevance
“…15,17,[43][44][45] Among the FMUSP students, there was an increase in recreational illicit drug use and in the use of nonprescription drugs. In addition, there was a marked change in the drug use profile among medical students.…”
Section: Drug Use At Fmuspmentioning
confidence: 99%
See 1 more Smart Citation
“…15,17,[43][44][45] Among the FMUSP students, there was an increase in recreational illicit drug use and in the use of nonprescription drugs. In addition, there was a marked change in the drug use profile among medical students.…”
Section: Drug Use At Fmuspmentioning
confidence: 99%
“…In reality, medical students have revealed significant vulnerability with regard to engaging in health risk behavior, 21 a paradoxical situation that has been a matter for concern worldwide [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and in Brazil. [14][15][16][17][18][19][39][40][41][42][43][44][45] A cross-sectional study on drug use among medical students at FMUSP, carried out in 1991, 1992 and 1993, found that alcohol, tobacco, marijuana, inhalants and tranquilizers were the drugs most commonly consumed. 39 The medical students consumed these drugs with the aim of improving academic performance, reducing fatigue, alleviating psychological tension and compensating for the lack of leisure time commonly observed among such students.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, alcohol is the most commonly used substance for these students, who underestimate its negative effects; thus, they are more exposed to risky situations and health hazards 5 . Some of the harmful consequences of hazardous use of alcohol in this population include: learning difficulties and academic problems with higher reprobation rates, such as reduced time dedicated to studies, non-attendance in classes, and poor academic performance; risky behaviors, such as increased frequency of unprotected sexual intercourse with different partners, sexual abuse, driving while intoxicated, traffic accidents, being intoxicated in public, fights, legal problems, and violent deaths; and future problems with psychoactive substances, including alcohol dependence and use of other psychoactive substances [2][3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Brazilian studies have also showed a significant cumulative lifetime use of alcohol 6,7,10,11 . In a conglomerate sample of 9,974 university students from the state of São Paulo, 62.1% reported use of alcohol in the preceding month 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation